Negotiating Care: Living Arrangements and Adults with Cognitive Disabilities in South Brazil, - Fietz, Helena (Développement Humain, Handicap et Changement Social / Human Development, Disability, and Social Change, 2020)
Assisted Living for adults with disabilities is a recent subject inboth Brazilian legislation and public debates. Although stillstigmatized by the idea that those who seek different livingarrangements for their children would be abandoning them, the concernwith both the autonomy of people with disabilities and the well-beingof the caregivers has prompted this theme to gain force in public andprivate spheres. Drawing from an ethnographic work with mothers ofadults with cognitive disabilitiesy from Porto Alegre, Brazil, whoconstituted a group to demand governmental action regarding assistedliving facilities, I propose a reflection on how such plea enables afurther discussion on the way disability and care are enacted. I arguethat by thinking of their trajectories through the care practices theyentail, one can track the moralities surrounding their experience ofmotherhood and how they are telling of the way disability is dealt within this specific time and place. Situating their claim within broaderdebates on institutionalization, I stress how their plea cannot beunderstood without a critical stand on ableism and the invisibility anddevaluation of care work.